Representasi G30S dalam Buku Teks Sejarah SMA Kurikulum 1994 Terbitan Erlangga Edisi Kedua: Analisis Wacana Kritis Roger Fowler - Alvina Cherisa Damayanti; Yuliati Yuliati (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
This study was motivated by the controversy surrounding the narrative of the September 30th Movement (G30S), which during the New Order era was presented in a one-sided manner and tended to vilify the Indonesian Communist Party (PKI) through various media, including history textbooks, thereby raising suspicions of ideological bias and political interests in their compilation, even though the publisher was a private company. Therefore, this study was conducted to analyze how the G30S is represented in the textbook “Sejarah Nasional Indonesia dan Umum: Untuk SMU Kelas 3,” published by Erlangga and authored by Badrika in 1997, by examining aspects of vocabulary, grammar, the representation of actors and events, as well as the ideology embedded within it. This aims to uncover the discourse constructions and interests behind the G30S narrative. The method used is qualitative research employing Roger Fowler’s Critical Discourse Analysis model, which focuses on language analysis as a social practice. The results indicate that the use of specific vocabulary and sentence structures creates a negative image of the PKI and a positive image of the military, while simultaneously limiting the reader’s perspective. Furthermore, the G30S events are represented in a linear manner, with the PKI as the primary actor and the military as the savior, without presenting the historical complexities. This discourse also contains New Order ideology that emphasizes the legitimacy of power and the instillation of Pancasila values. In conclusion, the textbook is not neutral but rather a product of discourse.